2021
DOI: 10.3390/fluids6040160
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Heat Transfer and Speed Air Flow on Performance of an Auto-Ventilated Disc Brake

Abstract: In the braking system, the heat dissipation generated by the friction between the disc and pad should be evacuated as quickly as possible. In this work, five common different automotive disc brakes were studied through mathematical theories of heat transfer and numerical methods using the ANSYS software. In addition, a direct comparison between experimental, theoretical, and simulation values found in the open literature was performed to propose a disc brake with an improved geometry in terms of dissipation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…It was observed that the vehicle braking deceleration as to the angle of descent increases, the decelerations increase because the gravitational resistance increases, considering that, in this particular case, it is also a propelling force. It is important to mention that the results of the Equations presented in Table 6 were used to develop 2D maps, considering Equations ( 13), (17), and (18) under different braking operating conditions. Currently, in many cases, the driver could not exert enough force to stop the vehicle at the ideal distance; therefore, the force is multiplied using levers or hydraulic circuits, thus obtaining a greater friction force.…”
Section: Mechanical and Dynamic Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It was observed that the vehicle braking deceleration as to the angle of descent increases, the decelerations increase because the gravitational resistance increases, considering that, in this particular case, it is also a propelling force. It is important to mention that the results of the Equations presented in Table 6 were used to develop 2D maps, considering Equations ( 13), (17), and (18) under different braking operating conditions. Currently, in many cases, the driver could not exert enough force to stop the vehicle at the ideal distance; therefore, the force is multiplied using levers or hydraulic circuits, thus obtaining a greater friction force.…”
Section: Mechanical and Dynamic Resultsmentioning
confidence: 99%
“…Depending on the force applied to the pedal, the higher efficiency of the process is obtained. On the other hand, the conditions of mathematical calculations are considered suitable concerning experimental and numerical calculations [17,29]. The mathematical analysis of the brake system is associated with braking force, resistance coefficient, rolling coefficient, deceleration, pedal force, peripheral speed, dissipated energy, braking deceleration, and dissipated power that aid to obtain the thermal calculations such as rise in temperature, surface temperature, and instantaneous temperature applying Newton's cooling law.…”
Section: Mathematical Equations Applied To Disc Brakesmentioning
confidence: 99%
See 3 more Smart Citations